The preparation of dual-functional hydrogel as the surface coating of plastics in biomedical applications - Nan Zhao; Bidhari Pidhatika (Majalah Kulit, Karet, dan Plastik, 2019)
Poly(2-ethyl-2-oxazoline) (PEOXA) is among polymers that have been reported to show anti-adhesive (bio-passive) behavior in numerous biomaterial applications. This work aimed to develop dual-functional hydrogel coatings, with PEOXA as hydrophilic polymer and benzophenone as cross-linker. PEOXA was partially hydrolyzed in acidic conditions to form PEOXA-m% EI that contains ethyleneimine (EI) groups. The EI groups were used as conjugation sites for incorporation of benzophenone (BP) molecules to PEOXA chains to form PEOXA-m% EIBP. Thin films of surface-attached polymer networks were generated from PEOXA-m% EIBP copolymers composed of PEOXA as platform and benzophenone as crosslinker units. The polymer became crosslinked through benzophenone units and forms a hydrogel as biopassive platform during irradiation with ultraviolet (UV) light. Laminin was incorporated into biopassive polymer network to allow for preparation of dual-functional hydrogel. NMR spectra indicated successful control of PEOXA partial hydrolysis and conjugation of benzophenone molecules to PEOXA chains. Ellipsometry and ATR-FTIR results showed that wavelength of UV light during C, H-insertion reaction influences stability of polymer network (hydrogel) on the substrate surface. XPS spectra verified that a stable film could be generated using suitable UV light during preparation of polymer network. Cell culture study on laminin/PEOXA-coated PMAA plastics showed dual-functional properties.